Identifikasi dan Analisis Alat Tangkap Rawai Kurau (Mini Long Line) yang Digunakan Nelayan di Kabupaten Bengkalis - Irwandy Syofyan; Isnaniah Isnaniah; M Rifa'i Siregar (Berkala Perikanan Terubuk, 2015)
This research conducted to known the construction and design of mini long line which were used by the fishermen on Bengkalis district, especially by the fishermen of Pambang village. The method used survey on the field, deep interviewed the fishermen and measured the fishing gear. The hook used is no.7. After eight years used (2004-2012) it was known that there was a changing on using sinker. Target fish was decrease in size. It was needed a comprehensive research about using mini long line due to the decreasing of fishing target fish size and the selectivity of gears.